Correlation Between Grammar Mastery and Speaking Ability of the Eighth Grade Students of SMP Negeri 15 Palu: Hubungan Antara Penguasaan Tata Bahasa dan Kemampuan Berbicara Siswa Kelas Delapan SMP Negeri 15 Palu - Susriani; Asri Hente; Andi Naniwarsih (Jurnal Kolaboratif Sains, 2021)
The objective of this research is to find out the correlation between Grammar Mastery and Speaking Ability of the eighth grade students of SMP Negeri15 Palu. The population of this research was the eighth grade students of SMP Negeri15 Palu. The sample was 28 students taken by applying random cluster sampling technique. The instruments of this research were the written and oral test. The researcher used the Pearson’s Product Moment Correlation Formula in analyzing the data. The result of both test showed that the was -0.102, degree of freedom (df) 26 (28-2), and was 0.374. In other words was lower than It means that there is a negative correlation between Grammar Mastery and Speaking Ability of the eighth grade students of SMP Negeri 15 Palu.